(untitled) (Global Journal of Management and Business Research, 2012)
What factors influence decision-making process in higher education institution? This paper presents the results of a case study of State University of Gorontalo, Indonesia that addressing to the question. The aims of this study were to identify and to analyse factors that influence decision-making process at the State University of Gorontalo. The study used descriptive quantitative method and data was collected using survey method. Sample of the study were 174 participants; consist of 129 lecturers and 45 administration staffs (n = 520). The quota of the sample was 25% from the population. Data were analysed using descriptive analysis. The result indicates that the five variable-factors have significant contribution to influence decision-making process at the State University of Gorontalo. The mean number of these five factors was 68.20%. The state of organization (with diversity value of 75.78%) was the dominant factor, followed by personality and skill of decision maker, which contributes up to 73.67%. Availability of Information provides to 73.30% and external condition to 63.98%. Other factors such as, type of problem within organization; the goal of decision-making and type of decision develop a total contribution of 54.29%.